Using the textbook “Practice Maths 1” to teach Maths in English to first graders at Minh Khai 1 primary school – Difficulties and some suggested solutions - Nguyễn, Thị Phúc (University of Languages and International Studies, 2017)
This study investigates the difficulties most teachers and students at Minh Khai 1 primary school have faced with in teaching and learning English for Maths by the textbook “Practice Maths 1”. The subject for this study consisted 4 teachers of English and (...)